Single molecule mass photometry reveals the dynamic oligomerization of human and plant peroxiredoxins - Liebthal, M; Kushwah, MS; Kukura, P; Dietz, K-J (Cell Press, 2021)
Protein oligomerization is central to biological function and regulation, yet its experimental quantification and measurement of dynamic transitions in solution remain challenging. Here, we show that single molecule mass photometry quantifies affinity and polydispersity of heterogeneous protein complexes in solution. We demonstrate these capabilities by studying the functionally relevant oligomeric equilibria of 2-cysteine peroxiredoxins (2CPs). Comparison of the polydispersity of plant and human 2CPs as a function of concentration and redox state revealed features conserved among all 2CPs. In addition, we also find species-specific differences in oligomeric transitions, the occurrence of intermediates and the formation of high molecular weight complexes, which are associated with chaperone activity or act as a storage pool for more efficient dimers outlining the functional differentiation of human 2CPs. Our results point to a diversified functionality of oligomerization for 2CPs and illustrate the power of mass photometry for characterizing heterogeneous oligomeric protein distributions in near native conditions.